2012
DOI: 10.1589/jpts.24.1259
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Thickness of Median Nerves Due to Excessive Use of Smartphones

Abstract: Abstract.[Purpose] The present study was intended to examine the effect of excessive use of smartphones on the carpal tunnel and median nerve in the wrist. [Subjects and Methods] A questionnaire was used to determine the degree of addiction to smartphones in 125 normal adults who used smartphones; then, ultrasonography of the median nerve, Phalen's tests, and reverse Phalen's tests were conducted on the subjects.[Results] Based on the results of the experiment, the thickness of the median nerve did not change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 20 publications
(16 reference statements)
3
30
0
2
Order By: Relevance
“…This may be due to frequent use of hands and fingers to operate the devices. This observation is consistent with previous studies indicating that excessive use of smartphones may adversely affect the median nerve and increase the probability of occurrence of CTS . Other studies found evidence for wrist abnormalities in computer users, such as restricted wrist range of motion and reduced sensory nerve function .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This may be due to frequent use of hands and fingers to operate the devices. This observation is consistent with previous studies indicating that excessive use of smartphones may adversely affect the median nerve and increase the probability of occurrence of CTS . Other studies found evidence for wrist abnormalities in computer users, such as restricted wrist range of motion and reduced sensory nerve function .…”
Section: Discussionsupporting
confidence: 93%
“…This observation was consistent with a previous study showing a positive correlation between cumulative hours of computer use and positive Tinel's and Phalen's signs in the right hand . Another study focusing on smartphone use also reported that positive Phalen's and reverse Phalen's test signs were associated with the degree of addiction to smartphones, periods of use, duration of use per day, and duration of continuous usage time . These clinical tests have been used to aid in the diagnosis of CTS, but it should be noted that the reported sensitivity and specificity of Tinel's and Phalen's tests vary from 30% to 100% …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations